Investigation of the Combustion Process of the Ignition Spark Discharge in a Pulsed Plasma Thruster - Igibayev Ж.Б.; Dosbolayev М.К. (Recent Contributions to Physics, 2025)
In this study, several experiments were conducted to optimize the ignition process and investigate its impact on the formation and development of the primary plasma flow. The ignition spark is generated when the graphite rod comes into contact with the grounded electrode. On the other hand, the graphite electrode is used as fuel in the pulsed plasma thruster (PPT). The dynamics of the pulsed discharge formation were recorded using the CMOS Phantom VEO710S high-speed camera, enabling the identification of key stages in plasma generation and acceleration. The emission spectrum of the discharge was obtained using the Optosky linear spectrometer, allowing for an analysis of the plasma composition and the determination of the thrust source. Changes in the current strength of the spark and main discharges over time were measured using a Rogowski coil.